OPTIMIZING LEARNING WITH TECHNOLOGY: ONLINE ATTENDANCE, AI, AND GESCHOOL AT MAN 2 PAYAKUMBUH THROUGH THE LOVE-BASED CURRICULUM (KBC) APPROACH - Yulastri, Weni; Zulfa, Zulfa; Hidayat, Hafiz; Hayati, Nova; Manurung, Kiki Hariani; Erlina, Erlina; Kaksim, Kaksim (Bhandar: Harvesting Community Service in Asia, 2025)
Educational transformation in the digital era demands the integration of technology into the teaching and learning process. This article describes a community service activity at MAN 2 Payakumbuh, which implemented three technological components—online attendance, artificial intelligence (AI), and the Geschool learning platform—using the Love-Based Curriculum (KBC) approach. This activity aimed to improve the effectiveness, efficiency, and humanization of the learning process. The Community Service method used was a participatory and collaborative approach with the school for two months. These activities included: a. Teacher workshops on the use of online attendance applications and Geschool. b. Training on AI Education Tools such as ChatGPT, Canva AI, and AI for creating teaching materials. c. Introduction and mentoring for the implementation of KBC, through character development based on the values of love, empathy, and spirituality in learning. An evaluation of this activity was also conducted. The results showed that the synergy between technology and the values of compassion in education had a positive impact on student learning motivation, teacher engagement, and improved classroom management.